Germ cell tumors of the ovary. (March 2011) - Schwartz, Peter E
Ovarian germ cell malignancies are rare tumors primarily affecting young women of reproductive age. Advances in modern therapy have allowed patients with primitive germ cell tumors (dysgerminoma, yolk sac tumor, choriocarcinoma and embryonal carcinoma) and biphasic or triphasic teratomas (dermoid cyst and immature teratoma) to preserve fertility and to be treated successfully, even when the disease is advanced. Monodermal teratomas and somatic-type tumors associated with biphasic and triphasic teratomas are even less common in occurrence and have a relatively good success rate, if limited to the ovary (stage I) when diagnosed, but have a poor overall survival when diagnosed in advanced stages. This article will review background information regarding these tumors, and advances in their diagnosis and management.